Patência do canal arterial no recém-nascido de pré-termo: experiência de um hospital terciário - Joana Cristina Gouveia Santos (2020)
Introduction: Patent ductus arteriosus (PDA) in preterm newborns (PTNB) has been associated with increased mortality and co-morbidities. This study aimed to characterize the population of preterm infants diagnosed with PDA and to identify predictive factors of response to medical treatment of PDA. Methods: An eight-year retrospective observational study was carried out, which included all PTNBs with gestational age between 24 and 32 weeks diagnosed with PDA, admitted to the HSJ Obstetrics Service. Univariate comparative analysis was performed, and models for predicting the effectiveness of PDA treatment with ibuprofen were explored by multivariate logistic regression analysis. Results: Were included in the study 114 cases and 33 were excluded, with a final sample of 81 PTNB with PDA. The univariable analysis revealed significant differences in the closure efficacy by medical treatment with ibuprofen in several variables, and a multivariate logistic regression model was obtained (discriminative capacity 72.2%, sensitivity 98.1%, specificity 57.1%), considering the effect of gestational age, type of delivery, need for diuretics treatment and platelet transfusion. Conclusion: This study allowed to characterize the population of preterm infants diagnosed with PDA and the identification of a predictive model that can aid to predict the effectiveness to the medical treatment and thus contribute to optimize the medical approach to the non-responders.